Non-malignant perforations: a study of various risk factors - Banu, Khamar Jaha (International Surgery Journal, 2016)
Background:Patients with peritonitis are amongthe most complex patients encountered in surgical practice. Despite advances in the management of gastrointestinal perforation, mortality remains high.Various studies have accessed the association of various risk factors with the outcome, but either with the single risk factor or an isolated post-operative complication. But there are additional risk factors that influence the outcome either directly or in a synergism.Thus there is a need to analyze the various determinants which can help us to plan the treatment strategy. Methods:50 patients were studied over a period of two years. All the patients were closely monitored till discharge or death. The association between the various risk factors and the outcome were correlated statistically using Pearson correlation co-efficient and its significance test. Results:The overall mortality was 16% and multi organ dysfunction syndrome was seen in 44% of the patients. The morality rate was higher in older individuals and longer the preoperative duration. Mannheim prognostic index was significantly higher in patients who developed multi organ dysfunction syndrome, though higher score was not significantly associated with mortality. Conclusions:The association between various risk factors studied and multi organ dysfunction and mortality did not achieve statistical significance. Multi organ dysfunction syndrome was associated with higher Mannheim peritonitis prognostic index but was not significantly associated with mortality. Mortality can be reduced by identifying the patients at risk and initiating immediate intensive approach in such patients.